2004
DOI: 10.1016/j.febslet.2004.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the binding and antioxidant properties of the plant flavonoid fisetin in model biomembranes

Abstract: Plant flavonoids are emerging as potent therapeutic drugs for free radical mediated diseases, for which cell membranes generally serve as targets for lipid peroxidation and related deleterious effects. Screening and characterization of these ubiquitous, therapeutically potent polyphenolic compounds, require a clear understanding regarding their incorporation and possible location in membranes, as well as quantitative estimates of their antioxidative and radical scavenging capacities. Here, we demonstrate the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 32 publications
2
66
0
2
Order By: Relevance
“…Fluorescence anisotropy (r) measurements were also performed, since this parameter serves as a sensitive indicator for monitoring fluorophore binding to motionally constrained regions of biological membranes (16,28). r is very low in fluid solution, where the fluorophore can freely rotate, and high for a rigid environment.…”
Section: Fluorescence Anisotropy Measurementsmentioning
confidence: 99%
“…Fluorescence anisotropy (r) measurements were also performed, since this parameter serves as a sensitive indicator for monitoring fluorophore binding to motionally constrained regions of biological membranes (16,28). r is very low in fluid solution, where the fluorophore can freely rotate, and high for a rigid environment.…”
Section: Fluorescence Anisotropy Measurementsmentioning
confidence: 99%
“…Currently, it is unclear what kind of molecules mediates this interaction. Flavonoids have been reported to bind membranes, so they could potentially associate with the tonoplast directly (Sengupta et al, 2004;Oteiza et al, 2005;Verstraeten et al, 2013;PawlikowskaPawlega et al, 2014). Some of the enzymes in the anthocyanin pathways have been shown to partially localize to the tonoplast (Saslowsky and Winkel-Shirley, 2001;Toda et al, 2012).…”
Section: Avis Arise From Microautophagy Of Cytoplasmic Anthocyanin Agmentioning
confidence: 99%
“…On the other hand penetration of hydrophobic bilayer core by a group of flavonoids and isoflavonoids was deduced by Arora et al [4] on the basis of fluorescence spectroscopic experiments. Intrinsic fluorescence properties of fisetin were used by Sengupta et al [7] to show that this molecule was localized and rigidly bound at the polar/apolar interfacial region of lipid bilayer. In a series of 1 H magic angel spinning NMR experiments it was shown that in fact flavonoid molecules are broadly distributed along the membrane normal with a maximal probability of localization close to polar/apolar interface [8].…”
Section: Introductionmentioning
confidence: 99%